Membangun Keterampilan Sosial: Peran Olahraga Jasmani dalam Perkembangan Sosial Anak Sekolah Dasar - Setiawati, Riska; Frimananda , Gilang Restu; Hasanah, Uswatun; Dian, Agesha Dinda Septa; Fitriyati, Nisa; Mulyana, Agus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Rather, it is an important element in a child's holistic education. Physical education and sports play an important role in supporting children's physical, social, emotional, cognitive, and healthy lifestyle growth and development. Through structured and planned physical activity, it helps improve the child's basic motor skills, strength, fitness, and overall health. The purpose of this study is to find out the important role of physical exercise in social growth and development in elementary school children. This study uses a literature study method, which begins by identifying topics to analysis and discussion related to the role of physical exercise in the social development of elementary school children. The main source of data in this article is the results of research published on google scholar. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The result of this study is that the role of physical exercise can encourage social interaction, cooperation, communication, sportsmanship, confidence, discipline, ability to manage emotions, focus, concentration, problem-solving skills, creativity, critical thinking, exercise habits, healthy diet, and awareness of the importance of physical and mental health.